2013
DOI: 10.1002/etc.2372
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 17α-ethynylestradiol, fluoxetine, and the mixture on life history traits and population growth rates in a freshwater gastropod

Abstract: Pharmaceutical and personal care products (PPCPs), some of which have endocrine-disrupting effects at environmentally relevant concentrations, have been detected in many surface waters. The authors evaluated the effects of 2 common endocrine disrupting PPCPs on the life history traits of the snail, Physa pomilia, using a life table response experiment with snails raised in environmentally relevant concentrations of 17α-ethynylestradiol (EE2), fluoxetine, or their mixture. Exposure to fluoxetine or the mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Because pharmaceutical compounds are often found at low levels and in mixtures from wastewater effluent, the potential additive, antagonistic, or synergistic effects of mixtures on aquatic ecosystems is important to understand. Luna et al [10] reported that mixtures of 17β-estradiol and the antidepressant fluoxetine decreased reproductive success of D. magna significantly more than either chemical compound alone.…”
Section: Introductionmentioning
confidence: 99%
“…Because pharmaceutical compounds are often found at low levels and in mixtures from wastewater effluent, the potential additive, antagonistic, or synergistic effects of mixtures on aquatic ecosystems is important to understand. Luna et al [10] reported that mixtures of 17β-estradiol and the antidepressant fluoxetine decreased reproductive success of D. magna significantly more than either chemical compound alone.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the effects at the population-level are dependent on the magnitude of the effect on a particular trait(s) but also on the relative influence of that trait on population dynamics (Forbes et al 2010, Forbes et al 2011, Rohr, Sager, et al 2006), as well as other features of the environment. Further, it is possible that subtle, non-significant effects on different traits, when integrated or combined using population models, can generate significant effects at the population level (Luna et al 2013). For studies in which surrogate communities are evaluated in mesocosms, the measurement endpoints (diversity, function) relate closely to system-level assessment endpoints.…”
Section: Current Challenges In Eramentioning
confidence: 99%
“…In this case, experiments on individual organisms that capture the effects of contaminants on key life history traits, such as rates of growth and development, fecundity, reproduction, or dispersal, and experiments on collections of organisms to estimate the strength of density dependence, can be valuable in estimating potential population-level effects (Forbes and Calow 2002a, Luna et al 2013, Martin et al 2013, Salice and Miller 2003, Stark 2005). Often, these experiments on key aspects of population dynamics are used to parameterize population-level models that can integrate these effects to more defensibly evaluate the consequences of a contaminant on populations (Erickson et al 2014, Luna et al 2013, Martin et al 2013, Salice and Miller 2003, Salice, Sample, et al 2011) than if any subset of these aspects were considered or if only a sub-individual- or individual-level approach was implemented. Although quantitative predictions from any mathematical model are only as good as its parameterization, model structure, and validation (Augusiak et al 2014, Grimm et al 2014), population models can perform well in predicting the impacts of contaminants on the population dynamics of organisms with short generation times (e.g.…”
Section: Population Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of these pharmaceuticals on the environment can be clearly demonstrated through the following examples; very tiny concentrations of 17α-ethynylestradiol and fluoxetine were able to cause a remarkable decline in the growth rates for Physa pomilia snails (Luna et al, 2013), traces of Clotrimazole that are similar to those present in nature rendered the algal 14α-demethylase unfunctional in laboratory trials (OSPAR-Commission, 2013) and diclofenac in low amounts (1 ug/L) caused deleterious effects on the kidney and intestine of the rainbow trout (Mehinto et al, 2010).…”
Section: Estrogenic Pharmaceutical Residuesmentioning
confidence: 99%